2015
DOI: 10.7314/apjcp.2015.16.16.6903
|View full text |Cite
|
Sign up to set email alerts
|

Burden of Cancers Related to Smoking among the Indonesian Population: Premature Mortality Costs and Years of Potential Life Lost

Abstract: Background: As smoking is the leading preventable cause of multiple diseases and premature cancer deaths, estimating the burden of cancer attributable to smoking has become the standard in documenting the adverse impact of smoking. In Indonesia, there is a dearth of studies assessing the economic costs of cancers related to smoking. This study aimed to estimate indirect mortality costs of premature cancer deaths and years of potential life lost (YPLL) attributable to smoking among the Indonesian population. Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 13 publications
2
21
0
Order By: Relevance
“…Premature Mortality Cost (PMC) is defined as parameters of the lost income caused by premature mortality based on human capital and obtained by calculating the number of mortality with life expectancy and average income [12]. Translation of the burden of diseases with the parameters PMC is able to provide evidence, so policy makers can understand that ultimately the state will still be harmed because of decreased public productivity and increased health costs to be borne by the government as a result of that risk factors [13].…”
Section: Discussionmentioning
confidence: 99%
“…Premature Mortality Cost (PMC) is defined as parameters of the lost income caused by premature mortality based on human capital and obtained by calculating the number of mortality with life expectancy and average income [12]. Translation of the burden of diseases with the parameters PMC is able to provide evidence, so policy makers can understand that ultimately the state will still be harmed because of decreased public productivity and increased health costs to be borne by the government as a result of that risk factors [13].…”
Section: Discussionmentioning
confidence: 99%
“…30,43 A major limitation of the present study is the limited number of patients although lung cancer is reported to be the number one cancer that kills men and the leading cause of economic burden in Indonesia. 44 The use of four-year data in this study could not even increase a significant number of data for inclusion, thus did not allow some more sophisticated statistical analyses to be conducted. Nonetheless, the number of Indonesian Journal of Clinical Pharmacy Volume 8, Issue 2, June 2019 samples in this study was quite representative since the total sampling technique was used, thus reducing the risk of missing potential insights from samples that were not included.…”
Section: Discussionmentioning
confidence: 99%
“…Risky Kusuma Hartono 1,2 *, Sabariah Abd Hamid 2 , Muhammad Hafizurrachman 1 According to the World Health Organization (WHO), 80% of the world's smokers live in low and middleincome countries and more than half of the world's smoking-addicted population resides in the Asia-Pacific region (WHO, 2015;Ho et al, 2018). In Indonesia, cancer due to smoke causes 74.440 people death with the dominant cases happens in man (95%) (Riskesdas, 2013;Kristina et al, 2015;Tandilittin, 2016). The warning label is no longer acts as a motivation factor to quit smoking immediately due to lack of credibility and inevitability related to the fatalism of the diseases on the label (Mead et al, 2015).…”
Section: Do the Number Of Cigarettes Smokes Per Day Contribute To Thementioning
confidence: 99%